Lingkungan Kerja dan Motivasi Kerja Guru di Kabupaten Kampar: Analisis Kuantitatif - Zuhri D (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2019)
The purposes of this study are to determine the effect of Work Environment on Job Motivation for teachers in all State Senior High Schools of Kampar Regency. The sample of this study was 255 teachers throughout Kampar Regency gathered from 92 State Senior High schools which were randomly selected. The results of this study indicate that Work Environment has a direct positive effect on teachers’ Job Motivation in all State Senior High Schools of Kampar Regency.